Biliary aminopeptidase-N and the cholesterol crystallisation defect in cholelithiasis. Issue 3 (September 1995) - Núñez, L; Amigo, L; Mingrone, G; Rigotti, A; Puglielli, L; Raddatz, A; Pimentel, F; Greco, A V; González, S; Garrido, J
Abstract : Several biliary proteins have cholesterol crystallisation promoting activity. One of these glycoproteins is aminopeptidase-N, a canalicular ectoenzyme. This study attempted to localise aminopeptidase-N along the biliary tree, to assess its concentration in a series of 98 patients subjected to abdominal surgery, 40 of them without gall stones, and to correlate its concentration with cholesterol crystal formation time of gall bladder bile. Aminopeptidase-N was isolated from purified native biliary vesicles. A specific polyclonal rabbit anti-aminopeptidase-N antibody was prepared for quantitative immunoblotting and for immunolocalisation. Tissue was obtained from liver biopsy specimens and from gall bladders removed at surgery because of gall stone disease. Aminopeptidase-N was immunolocalised to the apical membranes of hepatocytes and to the apical pole of ductular and gall bladder mucosal cells. The nucleation time of gall bladder bile was mean (SD) 4 (3) days in the gall stone group, compared with 21 (18) days in the control group (p < 0.001). Total absolute biliary protein and aminopeptidase-N concentrations were similar in both the control and gall stone patients. There was a reciprocal significant correlation, however, between the nucleation time and the relative aminopeptidase-N concentration (r = -0.35, p < 0.01) only in the gall stone group of patients. This study shows that this apical transmembrane ectoenzyme with cholesterol crystallisation promoting activity is present along the biliary tree and the hepatocyte. These findings support the concept that high concentrations or qualitative changes of biliary aminopeptidase-N contribute to cholesterol gall stone formation.